De‐occupation as planetary politics: On the Russian war in Ukraine. (27th January 2023) - Petryna, Adriana
Abstract: Russia's attempted occupation of Ukraine informs a concept of de‐occupation in an age of 21st‐century planetary wars. The tide of war crimes committed in Ukraine is beyond dispute, having been identified by legal scholars as genocidal attempts to condemn the very foundations of livelihood. I discuss the precedents that have allowed such crimes to occur and describe how Ukrainians are trying to counter these crimes, forming a particular kind of resistance that strikes against impunity. I locate impunity's persistence within post‐Soviet spheres, where solidarities among civilians who have been subject to Russian militarization complicate the view that the war in Ukraine is just another proxy war between superpowers. Given the dearth of architectures of peace and security to prevent genocide, de‐occupation emerges as a process in which de‐occupied people not only restore their territory but also play a central role in asserting less ruinous, more livable planetary futures.